Governos de esquerda na América Latina e a perspectiva da política externa dos EUA - Ayerbe, Luis Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Neste artigo, abordaremos a percepção do governo de George W. Bush sobre o significado da emergência na América latina de lideranças oriundas da esquerda, tendo como referência os desafios associados à agenda estadunidense na chamada Guerra Global contra o Terrorismo.

In this article, we discuss the perception of the government of George W. Bush on the significance of the emergence of leaders from the left in Latin America, with reference to the challenges associated with the U.S. agenda in the so-called Global War against Terrorism.
Left-wing governments in Latin America and the prospect of U.S. foreign policy
Keywords: América Latina; Nova esquerda; Política externa estadunidense; Governo George W. Bush; Latin American; New left. U.S. foreign policy; George W. Bush administration